Challenges for Middle School Science Teachers in Assessing Scientific Inquiry Skills: A Thematic Analysis - Kusuma, Mobinta; Wilujeng, Insih; Susongko, Purwo (International Journal of STEM Education for Sustainability, 2024)
Science learning assessment has always been challenging for science middle school teachers, especially when assessing students' scientific inquiry skills, which are essential to the science learning process. The study aims to highlight the challenges teachers confront when assessing high school pupils' capacity for scientific inquiry. It is a qualitative phenomenological study using thematic analysis techniques. Five middle school science teachers from junior high schools in Central Java participated in this study. Utilizing interviewing approaches, data was gathered. Using Clark Braun's thematic analysis methodologies, data analysis is carried out in four steps: (1) identifying the data, (2) performing coding, (3) creating themes, and (4) reviewing and defining the themes. This study shows that both internal and external factors might affect teachers' ability to undertake scientific inquiry research. The issue of obstacles teachers confront from the perspectives of students and learning systems is summarized by external variables. The researchers advised science teachers to engage in active, ongoing competence development to help them overcome challenges in evaluating scientific inquiries.